AN INVESTIGATION OF MACROLINGUISTIC ERRORS IN INDONESIAN EFL LEARNERS’ ESSAYS - Fanisa Fitrianti Putri; Dhafid Wahyu Utomo; Yusti Fargianti (JELLT (Journal of English Language and Language Teaching), 2021)
Abstract This present study tries to investigate macrolinguistic errors and to know the possible causes of the errors committed by Indonesian EFL Learners in their essay writing. This study employed qualitative approach with content analysis method. The data were taken from 40 university students’ essay and interview in one public university located in Banten province. The result of the data analysis reveals that the students commit seven types of error at the discoursal level and two types of error at the pragmatic level. In the discoursal level, the students committed run-on sentences, unawareness of logical relation, poor paragraph development, cohesion problem as well as coherence problem, improper use of discourse markers, and absence of parallel structure. In the pragmatic level, the researchers found miss-selection of lexical item and violation of the cooperative principles. Moreover, the possible causes of the errors included students have lack interest in writing; inadequate grammatical mastery; arranging ideas in a meaningful and logical order; lack of vocabulary and formulating their idea of writing. It is hoped that the result of this study can be the consideration for both the teachers when they design the material, and students to recognize their weaknesses in doing the writing and find the best solution to cope with this problem. Keywords: macrolinguistic error; students’ essay; Indonesia EFL Learners